The Business of Software: The Ontology of Paper. - Armour, Phillip G. (Communications of the ACM, 2009)
The article discusses software engineering in which software is used to develop software. Compilers convert a text form of instructions into machine instructions executable by a machine, the author states. Topics include integrated development environments (IDEs) which are mostly word processors with specific look-up processes, what the act of putting knowledge onto pieces of paper does to the knowledge itself, and computer-aided software engineering (CASE) tools used to store knowledge in a variety of formats including tables.